2003
DOI: 10.1016/s0960-9822(03)00087-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Mirror-Image Imitation in Asperger and High-Functioning Autistic Subjects

Abstract: Imitation is crucial for proper development of social and communicative skills. Here, we argue that, based on an error analysis of a behavioral imitation task, adult Asperger and high-functioning autistic subjects suffer from an intriguing deficit of imitation: they lack the natural preference for imitation in a mirror-image fashion. The imitation task consisted of a simple movement sequence of putting a pen with the left or right hand into a green or a blue cup using one of two possible grips. The subjects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 10 publications
11
56
1
Order By: Relevance
“…While there have been numerous studies examining imitation skills in autism, the vast majority of these studies have been conducted with children. Two studies conducted with teens found continued evidence of imitation impairments (Rogers et al, 1996;Loveland et al, 1994) and one other study of adults with ASD found significantly more errors and no benefits in using a mirror image to enhance performance (Avikainen et al, 2003). The current study found continued impairments in single and multiple step acts that involved both hand and face imitation, imitative acts that required both hands, and actions that involved meaningless movements.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…While there have been numerous studies examining imitation skills in autism, the vast majority of these studies have been conducted with children. Two studies conducted with teens found continued evidence of imitation impairments (Rogers et al, 1996;Loveland et al, 1994) and one other study of adults with ASD found significantly more errors and no benefits in using a mirror image to enhance performance (Avikainen et al, 2003). The current study found continued impairments in single and multiple step acts that involved both hand and face imitation, imitative acts that required both hands, and actions that involved meaningless movements.…”
Section: Discussionsupporting
confidence: 46%
“…School age children with autism also show imitation deficits (Hammes & Langdell, 1981;Ohta, 1987, Smith & Bryson, 1998Green et al, 2002;Jones & Prior, 1985). Such impairments persist into adolescence and adulthood although there are fewer studies that have examined this age group (Rogers et al, 1996;Avikainen et al, 2003;Hobson & Lee, 1999). Hobson and Lee (1999) found that teens with autism were able to imitate goal directed actions but failed to imitate the style in which the examiner performed the task with greater frequency than the control group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…chose the wrong cup) than effector errors (i.e. chose the wrong hand) and fewer effector errors than grip errors (Wohlschläger & Bekkering 2002b;Avikainen et al 2003). This pattern of results has often been taken as evidence for a hierarchical decomposition of the perceived act in imitation (cf.…”
Section: (B) Observation Of Goal-directed Actionsmentioning
confidence: 91%
“…Such errors imply that a person holds up the palm of his hand facing towards himself when he has observed the demonstrator facing his palm of the hand towards the other person. A number of studies reported reversal errors in imitation of actions without objects (Beadle-Brown, 2004;Dewey, Cantell, & Crawford, 2007;Ohta, 1987, Smith & Bryson, 1998Whiten & Brown, 1998) and actions with objects (Avikainen, Wohlschlager, Liuhanen, Hanninen, & Hari, 2003;Hobson & Lee, 1999;Meyer & Hobson, 2004) in children and adolescents with autism in contrast to non-autistic controls. Compared to appropriate controls, they were significantly less likely to imitate the orientation of an action in relation to the demonstrator's body.…”
mentioning
confidence: 99%